The value of high‐flow nasal cannula oxygen therapy in treating novel coronavirus pneumonia - Teng, Xiao‐bao (Eur J Clin Invest, 2020)
OBJECTIVE: This study aimed to investigate the value of high‐flow nasal cannula (HNFC) oxygen therapy in treating patients with severe novel coronavirus pneumonia (COVID‐19). METHODS: The clinical data of 22 patients with severe COVID‐19 were collected. The heart rate (HR), respiratory rate (RR) and oxygenation index (PO(2)/FiO(2)) at 0, 6, 24 and 72 hours after treatment were compared between the HFNC oxygen therapy group and the conventional oxygen therapy (COT) group. In addition, the white blood cell (WBC) count, lymphocyte (L) count, C‐reactive protein (CRP) and procalcitonin (PCT) were compared before and at 72 hours after oxygen therapy treatment. RESULTS: The differences at 0 hours between the two groups were not statistically significant. Compared with COT group,in the HFNC oxygen therapy group, HR, RR and PaO(2)/FiO(2) were better at 6 hours after treatment, PaO(2)/FiO(2) was better at 24 and 72 hours. After 72 hours, L and CRP had improved in the HFNC oxygen therapy group compared with the COT group, but the differences in WBC and PCT were not statistically significant. The length of stay in the intensive care unit (ICU) and the total length of hospitalization was shorter in the HFNC oxygen therapy group than in the COT group. CONCLUSION: Compared with COT, early application of HFNC oxygen therapy in patients with severe COVID‐19 can improve oxygenation and RR, and HFNC oxygen therapy can improve the infection indexes of patients and reduce the length of stay in the ICU of patients. Therefore, it has high clinical application value.